Survey on Teacher Online Teaching Competencies and Learner Satisfaction in Youtube Live Classes - Angelina, Lia; Chan, Shih Ping (Universitas Negeri Semarang, 2024)
With the advancement of technology, YouTube officially launched its live streaming feature, YouTube Live, in 2011. This initiated a trend of live-streamed Chinese language learning. This study focuses on the Richard Chinese YouTube channel, examining teacher's teaching competencies and learners' satisfaction factors. The research utilized a questionnaire to assess the impact of teaching competencies on learners' satisfaction, supplemented by interviews with the teacher. The questionnaire results indicated that among the three dimensions of online teaching competencies, class control competence was rated the highest on average. Among the seven dimensions of learner satisfaction, satisfaction itself had the highest average score. There was a significantly strong correlation between teaching competencies and learner satisfaction, suggesting that class control competence is the most crucial factor influencing learner satisfaction. In the interviews, Richard emphasized that he primarily teaches courses aligned with the HSK standards, aiming to help students pass the HSK exams. Richard pointed out that there is a wide range of Chinese proficiency levels among students, and many are not fully aware of their own language abilities. Despite the existing level divisions in the live classes, students often find the content either too difficult or too simple.